Antimicrobial peptides from the hemolymph of the prawn Macrobrachium rosenbergii - Samuthirapandian Ravichandran; Singaram Jeyalakshmi; Sathasivam Sudha; Ramasamy Anbuchezhian (Bangladesh Pharmacological Society, 2010)
The study was carried out to find the antimicrobial activity of hemolymph of Macrobrachium rosenbergii and to evaluate the antimicrobial compounds. The highest inhibition against Staphylococcus aureus, Lactobacillus vulgaris and Klebsiella pneumonia (12 mm) and antifungal activity was observed only against Fusarium moniliforme (11 mm). Antimicrobial peptide was characterized in molecular size ranging from 22 to 91KDa with antimicrobial activity against various infectious pathogens. Hemolymph plays a vital role in the disease prevention in crustaceans and there is no report on antimicrobial activities of the prawn M. rosenbergii.